Evaluation of an automated template-based treatment planning system for radiotherapy of anal, rectal and prostate cancer. (June 2022) - Calmels, Lucie; Sibolt, Patrik; Åström, Lina M.; Serup-Hansen, Eva; Lindberg, Henriette; Fromm, Anna-Lene; Persson, Gitte; Sjöström, David; Geertsen, Poul; Behrens, Claus P.
Highlights: Automated treatment planning system compared to manual planning. Equivalent plan quality between VMAT manually generated- and IMRT automatically generated plans. Evaluation of anal, prostate and rectum treatment plans. Generation of highly consistent IMRT automated plan within 2 to 3.5 min. Abstract: Background and purpose: The Ethos system has enabled online adaptive radiotherapy (oART) by implementing an automated treatment planning system (aTPS) for both intensity-modulated radiotherapy (IMRT) and volumetric modulated arc radiotherapy (VMAT) plan creation. The purpose of this study is to evaluate the quality of aTPS plans in the pelvic region. Material and Methods: Sixty patients with anal (n = 20), rectal (n = 20) or prostate (n = 20) cancer were retrospectively re-planned with the aTPS. Three IMRT (7-, 9- and 12-field) and two VMAT (2 and 3 arc) automatically generated plans (APs) were created per patient. The duration of the automated plan generation was registered. The best IMRT-AP and VMAT-AP for each patient were selected based on target coverage and dose to organs at risk (OARs). The AP quality was analyzed and compared to corresponding clinically accepted and manually generated VMAT plans (MPs) using several clinically relevant dose metrics. Calculation-based pre-treatment plan quality assurance (QA) was performed for all plans. Results: The median total duration to generate the five APs with the aTPS was 55 min, 39 min and 35 min for anal, prostate and rectal plans, respectively. The target coverage and the OAR sparing were equivalent for IMRT-APs and VMAT-MPs, while VMAT-Aps. demonstrated lower target dose homogeneity and higher dose to some OARs. Both conformity and homogeneity index were equivalent (rectal) or better (anal and prostate) for IMRT-APs compared to VMAT-MPs. All plans passed the patient-specific QA tolerance limit. Conclusions: The aTPS generates plans comparable to MPs within a short time-frame which is highly relevant for oART treatments.